Effects of light pollution on thermal tolerance of Chironomus riparius - Carmo, Joana Maria Sousa (2022)
Over the last few years, the expansion of urbanization has increased the levels of light pollution in natural aquatic ecosystems. Light pollution is caused by increased artificial light at night (ALAN), modifying natural light levels. ALAN disrupts circadian cycles, supressing the nocturnal production of the hormone melatonin. Urban freshwaters besides being exposed to light pollution are also experiencing warmer temperatures due to urban air and ground temperatures, paved surfaces, and decreased riparian vegetation (Urban heat island effect). With the presence of ALAN and warming, including effects of heat waves in urban ecosystems, it is of most importance to assess the combined effects of these two stressors and investigate if and how ALAN can modify the thermal tolerance of aquatic organisms. The aim of this work was to assess whether ALAN alters the upper thermal tolerance in the aquatic midge Chironomus riparius larvae and to investigate how ALAN interacts with heat on the development and physiology of the species. Moreover, I intended to further elucidate the physiological role of the hormone melatonin on this process. To assess the thermal tolerance, I determined the Critical thermal maximum limit (CTMax) of larvae (4th stage), after ten days of exposure to three different light intensities (0,1 and 10 lx) during nighttime with presence and absence of exogenous melatonin (0 and 1 μM). To detect the effects of these two combined stressors on the development of the species, I evaluated the emergence time of midge’s adults (female/male), body weight (female/male imagoes) and percentage of emergence after a chronic exposure (28 days) to three temperatures (20 ºC, 24 ºC and stimulated heat wave where organisms were exposed to 28 ºC for 6 days), under two ALAN treatments (0 and 10 lx during nighttime) and exogenous melatonin (1 μM), in a full factorial design. The results indicate that ALAN decreases the upper thermal tolerance of C. riparius larvae (CTMax) and that the supplementation of exogenous melatonin attenuated these effects. In chronic exposures, ALAN had no significant effect on the development of C. riparius. Increased temperatures, on the other hand, accelerated the development of the organisms (earlier emergence) but also led to lower body weight in adult insects. Exposure to the simulated heat wave increased mortality significantly. No effects of ALAN were observed for C. riparius life history traits but complex responses to exogenous melatonin were observed where effects of temperature were ameliorated (in case of emergence time) or increased (for body weight) in the presence of exogenous melatonin. I conclude that light pollution can change responses of C. riparius to thermal stress and that, as observed for many other aquatic invertebrates, short exposure to heat waves can have detrimental population level consequences. These results highlight the importance of studying the combined effects of warming and light pollution, two common and concomitant stressors in urban freshwater ecosystems. More research is needed not only to understand the physiological effects of exposure to ALAN as well as the role of melatonin in mediating the thermal tolerance of organisms. Moreover, these studies should also be validated in other invertebrate species. This and other studies will surely contribute to better predict the effects of warming and of global climatic changes in urban aquatic ecosystems.